2021
DOI: 10.1007/978-3-030-70210-6_32
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sound Properties and Oenological Characters by a Collaborative Sound Design Approach – Towards an Augmented Experience

Abstract: The paper presents a specific sound design process implemented upon a collaboration with an important stakeholder of the wine (Champagne) industry. The goal of the project was to link sound properties with oenological dimensions in order to compose a sonic environment able to realise a multisensory experience during the wine tasting protocol. This creation has resulted from a large scale methodological approach based on the semantic transformation concept (from wine words to sound words) and deployed by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Warm (chaud) and round (rond) are two sound attributes that seem to share many similarities in the description of sound as observed in some works (Bernays & Traube, 2014;Carron, 2016;Zacharakis et al, 2014). Studies conducted by three of the authors of this article have observed difficulties in distinguishing the two terms in professional conversations between sound designers and industrial partners (Carron et al, 2015;Misdariis et al, 2019). Although not thoroughly documented, this issue is persistent in sound design workshops based on verbal descriptions of sound characteristics.…”
Section: A S Human Beings W E a R E U Se D Tomentioning
confidence: 72%
See 1 more Smart Citation
“…Warm (chaud) and round (rond) are two sound attributes that seem to share many similarities in the description of sound as observed in some works (Bernays & Traube, 2014;Carron, 2016;Zacharakis et al, 2014). Studies conducted by three of the authors of this article have observed difficulties in distinguishing the two terms in professional conversations between sound designers and industrial partners (Carron et al, 2015;Misdariis et al, 2019). Although not thoroughly documented, this issue is persistent in sound design workshops based on verbal descriptions of sound characteristics.…”
Section: A S Human Beings W E a R E U Se D Tomentioning
confidence: 72%
“…Later, Kendall and Carterette (1993) used unipolar scales, or verbal attribute magnitude estimation (VAME), e.g., ''bright-non bright.'' Either using VAME or bipolar semantic scales to evaluate sounds, multiple subsequent studies have investigated the semantic dimensions of timbre (Alluri & Toiviainen, 2010;Nyka ¨nen et al, 2009;Pratt & Doak, 1976;Stepa ´nek, 2006;Traube, 2004;Zacharakis et al, 2014).…”
Section: A S Human Beings W E a R E U Se D Tomentioning
confidence: 99%
“…When the diverse literatures are taken together, it soon becomes clear how widespread the interest in sensory mapping/translation really is (cf. Misdariis et al, 2021 ; Trotta et al, 2020 , for a couple of other recent examples). Beyond its relevance to artistic performance or marketing/design contexts, we suggest that such a widespread interest might be rooted in the nature of the topic itself, which raises a number of intriguing (not to mention challenging) issues (see Daniels et al, 2010 ; Daniels & Naumann 2015 ).…”
Section: Sensory Translationmentioning
confidence: 97%
“…This paper deals only with the first question. The identification and description of these sounds must be linked with a shared meaning between the different actors of the project to allow a good communication between engineers, researchers and sound composers [5]. Several works were carried to identify methodologies to communicate on sounds in a sound design context with words [6], imitations [7], gestures [8] ...…”
Section: Introductionmentioning
confidence: 99%